Focused targeting against poverty evidence from Tunesia - Christophe Muller; Sami Bibi (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2005)
This paper introduces a new methodology to target direct transfers against poverty. Our method is based on observable correlates and on estimation methods that focus on the poor. Using data from Tunisia, we estimate `focused' transfer schemes that improve anti-poverty targeting performances. Post-transfer poverty can be substantially reduced with the new estimation method. The impact of these schemes on the welfare of the poor is also much stronger than the current food subsidies system in Tunisia. Finally, the obtained levels of under-coverage of the poor is so low that `proxy-means' focused transfer schemes becomes a realistic alternative to price subsidies, likely to avoid social unrest.
Keywords: D12; D63; H53; I32; I38; 330; Poverty; Targeting; Transfers; Armutspolitik; Öffentlicher Transfer; Tunesien